Social media as dialogue platforms for citizens and authorities of the Central Federal District's entities - V. V. Zotov; A. V. Gubanov (Цифровая социология, 2022)
This study examines the role of social and network resources in building dialogue with citizens on the example of subjects of the Central Federal District of regional government bodies. The study is based on monitoring the network space of public communications formed around the accounts of the authorities of the subjects of the Central Federal District. The data obtained were compared with the results of similar monitoring in 2019, as well as the results of a sociological survey on civic engagement of the population on social networks.As a general rule, the presence of two key network resources in each of the regions was noted – the personal accounts of the head of the region and the official pages of governments (administrations). These resources act as a network “showcase”, are efficiently administered and are consistently filled with well-developed content. Monitoring data make it possible to confirm the presence in the network space of public communications of a fully developed pool of government accounts in popular social media users among domestic Internet users of social media. But at the same time, a decrease in user involvement in the socio-network space of public communications around government accounts is observed for all regions under study.The information field of each region of the Central Federal District is unique, its actual structure depends on a number of objective factors, such as the level of penetration of various social networks into the audience of Internet users, the activity of large network actors (bloggers, media, popular public), the features of network interaction of ordinary users. Ultimately, the totality of external conditions should predetermine the model of behavior of authorities in social networks.The introduction of the “Incident Management” system has had a positive impact on the situation, through which citizens’ appeals are not only accepted and processed, but also sent to target authorities, which are obliged to provide a response to the applicant via social networks.The conclusion of the study presents the authors’ recommendations, which, in our opinion, will optimise the operation of the network of official accounts of the entities of the Central Federal District.